The formal architecture of identity in Nancy Huston's L'Empreinte de l'ange - Kate Averis (Francosphères)
This article analyses Huston's 1998 novel, L'Empreinte de l'ange, which explores language's fundamental role in transnational mobility, and how the daily migration between French and another language impacts on the negotiation of identity for cultural others in France. This analysis demonstrates how linguistic alterity disrupts the apparently easy coincidence of language, community, identity, and belonging. The first section examines Huston's use of language as both a narrative theme and strategy in the representation of the interstitial subjectivity characteristic of transnational mobility. The second part turns to Huston's concern with her legitimacy as a non-native Francophone writer within the canon of French literature. The conclusion posits the notion that the highly visible formal architecture of Huston's novel can be seen as a deliberate strategy to enact and unravel the links between language, writing, and transnational Francophone identity.Le présent article analyse L'Empreinte de l'ange (1998) de Nancy Huston, qui explore le rôle fondamental du langage dans le processus de mobilité transnationale, ainsi que l'impact identitaire de la migration quotidienne entre le français et une autre langue pour des résidents en France nés en dehors de l'Hexagone. Cette analyse démontre l'effet bouleversant de l'altérité linguistique sur la continuité entre langage, communauté, identité, et appartenance. Dans un premier temps, nous analysons l'emploi du langage comme thème de la narration ainsi que comme stratégie narrative dans la représentation de la subjectivité interstitielle, qui est caractéristique de la mobilité transnationale. Dans un deuxième temps, nous étudions la préoccupation de l'auteur concernant sa légitimité en tant qu'auteur francophone non-autochtone au sein de la littérature française. Cette analyse permet de conclure que la structure formelle extrêmement visible du roman vise à apporter un éclairage sur les liaisons entre le langage, l'écriture, et l'identité francophone et transnationale.